Norma agama Nasrani dalam paradigma usul fiqh inklusif - Moh Dahlan (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2014)
The purpose of this study is to explore the historical roots of the legal norms (religion) Islam is built by the Prophet Muhammad and also explore the norms of Christianity which became an integral part of the legal sources of usul fiqh inclusive paradigm. The theoretical framework of this study is to use blending approach the horizon (fushion of horizons) in the hermeneutics of Hans George Gadamer and shar’ man qablana theory. The results show that there is continuity of the norms of Christianity in the development discourse of Islamic law/jurisprudence, so that the norms of the Christian religion can be a source of usul fiqh paradigm inclusive. The character of legal norms/Islam which has the accommo- dative properties -in addition to corrective attitude towards ancient religions norms - be a strong indicator continuity. In this continuity, Imam Abu Hanifa, Imam Ahmad Ibn Hanbal, Muhammad Abduh, Rashid Ridla, Nurcholish Madjid and Shihab acknowledge the continuity of Christianity norms in the development of legal discourse such a ban “alcohol”, the command “fasting” and “ do good to others”. In the context of pluralism in Indonesia, usul fiqh iklusif paradigm is necessary to build an inclusive legal discourse-dynamic.   Tujuan kajian ini adalah untuk mendalami akar sejarah norma hukum (agama) Islam yang dibangun oleh Nabi Muhammad Saw.. dan juga mendalami norma agama Nasrani yang menjadi bagian integral dari sumber hukum paradigma usul fikih inklusif. Adapun kerangka teori kajian ini adalah menggunakan pendekatan pembauran cakrawala (fusion of horizons) dalam hermeneutika Hans George Gadamer dan teori shar’ man qablana. Hasil kajian menunjukkan bahwa ada kontinuitas norma-norma agama Nasrani dalam pembangunan wacana hukum Islam/ fiqh, sehingga norma-norma agama Nasrani dapat menjadi sumber dalam paradigma usul fiqh inklusif. Karakter norma hukum/ agama Islam yang memiliki sifat akomodatif –di samping sikap korektif terhadap norma agama-agama terdahulu- menjadi indikator kuat adanya kontinuitas. Dalam hal kontinuitas ini, Imam Abu Hanifah, Imam Ahmad Ibn Hambal, Muhammad Abduh, Rasyid Ridla, Nurcholish Madjid dan Alwi Shihab mengakui adanya kontinuitas norma-norma agama Nasrani dalam pembangunan wacana hukum fikih/agama Islam misalnya larangan “miras”, perintah “puasa” dan “ berbuat baik kepada sesama”. Dalam konteks kemajemukan di Indonesia, paradigma usul fiqh iklusif ini diperlukan dalam membangun wacana hukum fikih yang inklusif- dinamis.